Investigasi Kandungan Parasetamol Pada Jamu Pegal Linu di Kawasan Pasar Malam Kota Banjarmasin Kalimantan Selatan - Rahmadani Rahmadani; Tuti Alawiyah (Jurnal Farmasi & Sains Indonesia, 2021)
Herbal products are very well known by the people of Indonesian since ancient times in an effort to prevent disease, treat and restore fitness. Medicinal Chemicals (MCs) are often added to herbal preparations to increase the efficacy of herbal medicine and provide a more instant herbal effect. With an uncertain dose will cause very serious side effects for health. This research was conducted with 5 samples of herbal aches and pains in the night market area of Banjarmasin. The test was carried out by qualitative analysis using Thin Layer Chromatography (TLC) and quantitative analysis using UV-Vis Spectrophotometer. The results of the qualitative test showed the presence of paracetamol BKO in sample C and sample D and the results of the quantitative test resulted in sample C of 8.13 mg/Kg and sample D of 6.28 mg/Kg